Preconditioning with Cathodal High-Definition Transcranial Direct Current Stimulation Sensitizes the Primary Motor Cortex to Subsequent Intermittent Theta Burst Stimulation - Wenjun Dai; Yao Geng; Hao Liu; Chuan Guo; Wenxiang Chen; Jinhui Ma; Jinjin Chen; Yanbing Jia; Ying Shen; Tong Wang (Neural Plasticity, 2021)
Noninvasive brain stimulation techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) can induce long-term potentiation-like facilitation, but whether the combination of TMS and tDCS has additive effects is unclear. To address this issue, in this randomized crossover study, we investigated the effect of preconditioning with cathodal high-definition (HD) tDCS on intermittent theta burst stimulation- (iTBS-) induced plasticity in the left motor cortex. A total of 24 healthy volunteers received preconditioning with cathodal HD-tDCS or sham intervention prior to iTBS in a random order with a washout period of 1 week. The amplitude of motor evoked potentials (MEPs) was measured at baseline and at several time points (5, 10, 15, and 30 min) after iTBS to determine the effects of the intervention on cortical plasticity. Preconditioning with cathodal HD-tDCS followed by iTBS showed a greater increase in MEP amplitude than sham cathodal HD-tDCS preconditioning and iTBS at each time postintervention point, with longer-lasting after-effects on cortical excitability. These results demonstrate that preintervention with cathodal HD-tDCS primes the motor cortex for long-term potentiation induced by iTBS and is a potential strategy for improving the clinical outcome to guide therapeutic decisions.